Specification Languages for Preserving Consistency between Models of Different Languages - Kramer, Max Emanuel (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2019)
When complex IT systems are being developed, the usage of several programming and modelling languages can lead to inconsistencies that yield faulty designs and implementations. To address this problem, this work contributes a classification of consistency preservation challenges and an approach for preserving consistency. It is formalized using set theory and monitors changes to avoid matching and diffing problems. Three new languages that follow this preservation approach are presented.